Genome-wide identification of EuUSPs in Eucommia ulmoides and the role of EuUSP16 in rubber biosynthesis - Long, Shangmei; Yang, Jiang; Wang, Hongling; Chen, Xi; Zhao, De-gang; Zhao, Yichen (Frontiers in Plant Science, 2025)
Eucommia ulmoides Oliv., a Tertiary period relict tree species endemic to China, is a rubber-producing plant valued for both medicinal and edible applications. E.ulmoides rubber is a high-quality natural rubber prized for its excellent elasticity, abrasion resistance, and insulation properties, leading to broad industrial applications. Previous research identified the EuUSP16 gene, encoding a protein containing E.ulmoides rubber particle protein peptides. While overexpression of EuUSP16 in tobacco enhanced drought tolerance, its role in E.ulmoides rubber biosynthesis remained undefined. In this study, we identified 29 EuUSP genes at the whole-genome level in E.ulmoides. Following low-temperature and drought treatments, the expression level of the EuUSP16 gene was found to be positively correlated with changes in rubber content (p<0.05), suggesting its potential regulatory role in rubber synthesis. In E.ulmoides subjected to Agrobacterium-mediated EuUSP16 gene overexpression or silencing, the expression levels of key E.ulmoides rubber biosynthesis enzyme genes, such as EuFPS1, exhibited corresponding increases and decreases, respectively. Furthermore, rubber content in EuUSP16-overexpressing callus increased by 254.51% compared to wild-type callus. These findings indicate that EuUSP16 regulates E.ulmoides rubber biosynthesis by modulating the expression of these genes. The 1,967 bp promoter region upstream of the EuUSP16 ATG start codon contains several responsive elements, including MBS (MYB-binding site; CAACTG), LTR (low-temperature responsive element; CCGAAA), ABRE (ABA-responsive element; ACGTG), and a Dof transcription factor binding motif (AAAG). Promoter activity assays showed that EuUSP16 promoter activity was induced by low temperature and drought but repressed by abscisic acid (ABA) treatment. Furthermore, using yeast one-hybrid screening, we identified a Cys2-Cys2 zinc finger domain-containing transcription factor, designated EuDof. Interaction analysis revealed that the EuDof transcription factor enhances the activity of the EuUSP16 promoter. The binding of EuDof to the EuUSP16 promoter was enhanced under low temperature and drought stress but inhibited by ABA. Collectively, this study provides crucial insights into the regulatory mechanism of EuUSP16 in E.ulmoides rubber biosynthesis.